Research on security-constrained unit commitment based on an improved ordinal optimization algorithm - Zhang, Zhi; Xu, Guobin; Yang, Nan (Frontiers in Energy Research, 2023)
Research on efficient and accurate algorithm for solving the problem of security constrained unit commitment (SCUC) is of great significance to the development of intermittent renewable energy and electricity marketization. On the basis of existing constrained ordinal optimization (COO), this paper proposes an improved ordinal optimization (OO) algorithm which can be applied to solving the SCUC problems. In order to solve the crude model and precise model, discrete variable identification strategy and effective security constraint reduction strategy are respectively adopted. Compared to the traditional method, this modified OO algorithm gives full play to the traditional OO in computational efficiency while further enhances the compactness and reduces the computation redundancy. The correctness and effectiveness of the proposed algorithm are verified by the IEEE118 simulation results.